NUMERICAL ANALYSIS OF POST RAINFALL SLOPE STABILITY WITH REINFORCEMENT CASE STUDY IN PURWOSARI KULON PROGO - Yuli Fajarwati; Zalfa Nabila; Dian Eksana Wibowo; Endaryanta Endaryanta (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2026)
Continuous rainfall over several days caused a landslide along Jalan Penggung, Purwosari Village, Girimulyo District, Kulon Progo Regency. This study was conducted to analyse slope stability under rainfall conditions and to evaluate reinforcement alternatives including soil nailing, ground anchors, and gabions. The slope topography was obtained from DEMNAS data and processed using AutoCAD Civil 3D, while soil parameters were derived from laboratory testing. Rainfall data were obtained from the JAXA satellite and effective rainfall infiltration was calculated using the SCS-CN method. The infiltration was modelled using SEEP/W and the slope stability was subsequently analysed using SLOPE/W with and without reinforcement. The analysis of the existing slope without seismic loading produced an initial safety factor (SF) of 0.922, which decreased to 0.801 after one day of rainfall. When seismic loading was considered, the initial SF was 0.639 and further decreased to 0.550 after one day. These results indicate that the existing slope is unsafe under both static and seismic conditions, making reinforcement necessary. The SF of the slope increased by 118% with soil nailing, 128% with anchors, and 14% with gabions under static conditions. Under seismic loading, soil nailing increased the SF by 101%, anchors by 110%, and gabions by 15%. These findings demonstrate that soil nailing and anchors can improve slope stability to safe levels, whereas gabions are ineffective for the studied slope conditions.